Mapping of multiple criteria for priority setting of health interventions: an aid for decision makers - Tromp Noor; Baltussen Rob (BMC, 2012)
Abstract Background In rationing decisions in health, many criteria like costs, effectiveness, equity and feasibility concerns play a role. These criteria stem from different disciplines that all aim to inform health care rationing decisions, but a single underlying concept that incorporates all criteria does not yet exist. Therefore, we aim to develop a conceptual mapping of criteria, based on the World Health Organization's Health Systems Performance and Health Systems Building Blocks frameworks. This map can be an aid to decision makers to identify the relevant criteria for priority setting in their specific context. Methods We made an inventory of all possible criteria for priority setting on the basis of literature review. We categorized the criteria according to both health system frameworks that spell out a country's health system goals and input. We reason that the criteria that decision makers use in priority setting exercises are a direct manifestation of this. Results Our map includes thirty-one criteria that are distributed among five categories that reflect the goals of a health system (i.e. to improve level of health, fair distribution of health, responsiveness, social & financial risk protection and efficiency) and leadership/governance one category that reflects feasibiliy based on the health system building blocks (i.e. service delivery, health care workforce , information, medical products, vaccines & technologies, financing and). Conclusions This conceptual mapping of criteria, based on well-established health system frameworks, will further develop the field of priority setting by assisting decision makers in the identification of multiple criteria for selection of health interventions.